Interleukin 35 Delays Hindlimb Ischemia-Induced Angiogenesis Through Regulating ROS-Extracellular Matrix but Spares Later Regenerative Angiogenesis - Fu, Hangfei; Sun, Yu; Shao, Ying; Saredy, Jason; Cueto, Ramon; Liu, Lu; Drummer, Charles; Johnson, Candice; Xu, Keman; Lu, Yifan; Li, Xinyuan; Meng, Shu; et al. (Frontiers in Immunology, 2020)
Interleukin (IL) 35 is a novel immunosuppressive heterodimeric cytokine in IL-12 family. Whether and how IL-35 regulates ischemia-induced angiogenesis in peripheral artery diseases are unrevealed. To fill this important knowledge gap, we used loss-of-function, gain-of-function, omics data analysis, RNA-Seq, in vivo and in vitro experiments, and we have made the following significant findings: i) IL-35 and its receptor subunit IL-12RB2, but not IL-6ST, are induced in the muscle after hindlimb ischemia (HLI); ii) HLI-induced angiogenesis is improved in Il12rb2−/− mice, in ApoE−/−/Il12rb2−/− mice compared to WT and ApoE−/− controls, respectively, where hyperlipidemia inhibits angiogenesis in vivo and in vitro; iii) IL-35 cytokine injection as a gain-of-function approach delays blood perfusion recovery at day 14 after HLI; iv) IL-35 spares regenerative angiogenesis at the late phase of HLI recovery after day 14 of HLI; v) Transcriptome analysis of endothelial cells (ECs) at 14 days post-HLI reveals a disturbed extracellular matrix re-organization in IL-35-injected mice; vi) IL-35 downregulates three reactive oxygen species (ROS) promoters and upregulates one ROS attenuator, which may functionally mediate IL-35 upregulation of anti-angiogenic extracellular matrix proteins in ECs; and vii) IL-35 inhibits human microvascular EC migration and tube formation in vitro mainly through upregulating anti-angiogenic extracellular matrix-remodeling proteins. These findings provide a novel insight on the future therapeutic potential of IL-35 in suppressing ischemia/inflammation-triggered inflammatory angiogenesis at early phase but sparing regenerative angiogenesis at late phase.